Performance Evaluation of Exotic and Local Landraces of Tomatoes for the Mid-Hill Conditions of Nepal - Tek Prasad Gotame; Ishwori Prasad Gautam; Dipendra Ghimire; Surendra Lal Shrestha (Turkish Journal of Agriculture: Food Science and Technology)
The productivity of tomato in Nepal is very low due to lack of high yielding, disease and pests resistant varieties. An experiment was carried out to evaluate horticultural traits of 50 genotypes obtained from World Vegetable Centre (WorldVeg), Taiwan and SAARC region, and local collections during March to August 2020 in open field conditions at National Horticulture Research Centre, Khumaltar, Lalitpur. The objectives were to identify promising open-pollinated tomato cultivars for high yield, appropriate fruit size, and disease resistant. The experiment was carried out in a randomized complete block design with three replications. Results showed significant differences in yield and yield attributing characters including virus infection. The highest yield (39.6 mt ha-1) was produced by HRA43 and it was followed by HRA33 (26.4 mt ha-1). Among the WorldVeg OP lines, AVTO1429 produced the highest yield (16.21 mt ha-1) and it was followed by AVTO1717 (12.95 mt ha-1), AVTO0922 (11.83 mt ha-1) and AVTO1219 (11.7 mt ha-1) respectively. Most of the WorldVeg lines performed better than the check variety ‘Pusa Ruby’. Genotype HRA43, Red Local and Sindhupalchock Local were not affected by virus while Yellow Local showed 3.3% infection. Among the WorldVeg lines, AVTO1712 (20%), AVTO1717 (20%) and AVTO1718 (13%) and AVTO1219 (15%) showed less than 20% virus infection in the open field conditions. Cluster analysis using the unweighted paired group method with arithmetic mean showed that cluster-1 was the largest cluster comprised of 40 genotypes followed by cluster-2 and cluster-4. Genotypes from cluster-4 showed the higher fruit yield (25.1 mt ha-1) and resistant to the virus and the highest number of fruits per plot (1978 in 4.5 m2 area). The yield was low in cluster-1 which could be due to the heavy rainfall during the vegetative and reproductive stages. Genotypes Red Local and Sindhupalchock Local could be used in future tomato breeding program due to their resistant to TYLCV, higher potential yield and highest plant vigour in open field conditions at the mid-hill of Nepal. Considering the overall performance, genotype HRA43, HRA33 and AVTO1429 were promising lines with performance for yield and other horticultural traits.